Distance determination to six nearby galaxies using type IIP supernovae. Issue Volume 9:Issue S296(2013) (29th January 2014) - Bose, Subhash; Kumar, Brijesh
Abstract: We use early optical photometric and spectroscopic data of six Type-IIP SNe to derive distances to their host galaxies using the expanding photosphere method (EPM). Our sample consists of luminous to sub-luminous SNe 1999gi, 2004et, 2005cs, 2008in, 2009md and 2012aw; having absolute V-magnitudes from -17 to -15 and host galaxy distances from 5 to 22 Mpc. The SN 2008in is peculiar in nature showing dual behavior of a luminous as well as sub-luminous event. The EPM distances for four of the events in our sample are derived for the first time. We take utmost care in minimizing the errors arising from photospheric velocity determination and the broadband filter responses, hence leaving out uncertainty in dilution factor models as the only major source of error. Our preliminary results indicate that EPM-derived distances using Dessart model is found to be consistent with the distances quoted in the literature. We find that EPM method is applicable only to the early (<50 d) photometric data of supernovae and dense spectroscopic data is necessary to estimate accurate distances.